Amino acid transporters and nutrient-sensing mechanisms: new targets for treating insulin-linked disorders?. (25th October 2007) - Reynolds, B.; Laynes, R.; Ögmundsdóttir, M.H.; Boyd, C.A.R.; Goberdhan, D.C.I.
Abstract : The IIS (insulin/IGF (insulin-like growth factor) signalling) cascade has an important role in regulating normal development and physiology, as evidenced by its effects in a host of major human diseases including cancer, Type 2 diabetes and neurodegeneration. Recently, it has become clear that multiple types of local nutrient-sensing mechanisms have an impact on cellular insulin-sensitivity through the downstream kinase TOR (target of rapamycin). In vivo analysis in flies has surprisingly highlighted PATs (p roton-assisted a mino acid t ransporters) as having a uniquely potent role in regulating IIS/TOR activity and growth, potentially via a novel signalling mechanism. Other molecules such as the heterodimeric amino acid transporter, CD98, which provides the principal route for cellular uptake of leucine, an amino acid implicated in regulating TOR, also appear to have important effects. As our understanding of how nutrient sensing has an impact on IIS/TOR increases, novel targets to modulate aberrant IIS in disease are likely to emerge, which could complement current strategies designed to block kinases in this pathway.